The Effect of Corporate Water Disclosure on Financial Performance: Evidence from South Africa - NYAHUNA, Thomas; DOORASAMY, Mishelle (PT Keberlanjutan Strategis Indonesia, 2023)
The significance of corporate water disclosure must be considered. From a legitimacy theory perspective, this research evaluated the relationship between corporate water disclosure and the financial performance of 30 Johannesburg Stock Exchange (JSE) listed companies from 2017 to 2021. A quantitative study was adopted based on a longitudinal approach. The study's population involved all companies appearing on the JSE Responsible Investment Index in South Africa. As a result, 14 companies were sampled on the South Africa FTSE/JSE Responsible Investment Index. The findings indicate that financial performance indicators, namely return on assets, net profit margin, and earnings per share, had a significant positive relationship with corporate water disclosure. However, the findings exhibit that return on equity has a negative relationship with corporate water disclosure. Capital intensity was used as the control variable. It was inferred that to amplify return on assets, net profit margin, and earnings per share, JSE-listed companies should commit themselves to disclosing water-related initiatives and management. It acts as a source of motivation for companies that can increase financial performance by focusing on disclosing water-related issues.